2018
DOI: 10.1186/s12864-018-5137-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing analysis of multiple Salmonella serovars provides insights into phylogenetic relatedness, antimicrobial resistance, and virulence markers across humans, food animals and agriculture environmental sources

Abstract: BackgroundSalmonella enterica is a significant foodborne pathogen, which can be transmitted via several distinct routes, and reports on acquisition of antimicrobial resistance (AMR) are increasing. To better understand the association between human Salmonella clinical isolates and the potential environmental/animal reservoirs, whole genome sequencing (WGS) was used to investigate the epidemiology and AMR patterns within Salmonella isolates from two adjacent US states.ResultsWGS data of 200 S. enterica isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
83
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 65 publications
11
83
1
1
Order By: Relevance
“…Similar to the results of Tyson et al (2016) and Pornsukarom et al (2018), discrepancies were observed for genotypic prediction of STR resistance even after broth and agar microdilution testing. A study by Koskiniemi et al (2011) found activation of a chromosomally encoded adenyl transferase (aadA) combined with mutations affecting the electron transport chain (ETC) resulted in increased STR resistance.…”
Section: Activation Of Str Resistance In Salmonella Spp Occurs In MIsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar to the results of Tyson et al (2016) and Pornsukarom et al (2018), discrepancies were observed for genotypic prediction of STR resistance even after broth and agar microdilution testing. A study by Koskiniemi et al (2011) found activation of a chromosomally encoded adenyl transferase (aadA) combined with mutations affecting the electron transport chain (ETC) resulted in increased STR resistance.…”
Section: Activation Of Str Resistance In Salmonella Spp Occurs In MIsupporting
confidence: 71%
“…Specific serotypes and AMR profiles can be linked to food commodities which can vary depending on antimicrobial usage for food production in different countries (Butaye et al, 2006;Zhao et al, 2007;Hong et al, 2016;Yoon et al, 2017). As such, the resistance profile and serotype of a Salmonella isolate can provide clues as to the epidemiology of an infection (Pornsukarom et al, 2018). Some examples include MDR S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
“…Our results (Figures 1, 2, 4) demonstrated that the core genome analysis as performed by Hindermann et al (2017) is not discriminative enough to determine whether or not the S. Infantis strains from Switzerland are really clustered together with, and could be epidemiologically related to strains from Hungary, Japan, Italy, United States, and Israel. Our results also indicated that the analysis of core genomes provides less detailed information about the different genetic lineages as discussed by Pornsukarom et al (2018). In this respect, the phylogenetic reconstructions based on cloud genes (Figures 3, 4) remarkably differ also from that based on the whole genomes (Figure 1).…”
Section: Discussionmentioning
confidence: 53%
“…Few studies have been conducted to identify genetic factors associated with Salmonella serovars isolated from swine using WGS [19,20]. In order to understand the genetic variations among different Salmonella serovars, the WGS of fourteen Salmonella serovars isolated from swine and swine swab were analyzed.…”
Section: Introductionmentioning
confidence: 99%